PCSK9 Contributes to the Cholesterol, Glucose, and Insulin2 Homeostasis in Seminiferous Tubules and Maintenance of Immunotolerance in Testis - Pelletier, R.-Marc; Layeghkhavidaki, Hamed; Seidah, Nabil G.; Prat, Annik; Vitale, María L. (Frontiers in Cell and Developmental Biology, 2022)
ABSTRACT The PCSK9 contribution to cholesterol and immunotolerance homeostasis and response to glucose, and insulin in testis and hypophysis were studied using Pcsk9-deficient (-/-) and transgenic (Tg(PCSK9)) mice, and diabetic, obese ob/ob and db/db mice. The spermatids/spermatozoa acrosome, peritubular vessels, and epididymal adipocytes were PCSK9- and LDL-R-positive. The pro-PCSK9/PCSK9 ratio was high in interstitial tissue-fractions (ITf) and spermatozoa and low in seminiferous tubule-fractions (STf) in normal adult mice. This ratio decreased in ITf in ob/ob and db/db mice but increased in tubules in ob/ob mice. Deleting pcsk9 lowered cholesterol in serum but increased testicular cholesterol. Furthermore, HMGCoA-red, ACAT-2 and LDL-R turnover increased whereas SR-BI decreased in ITf; in tubules, ABCA1 decreased and 160kDa LDL-R increased in Pcsk9-/- mice. Excess testicular cholesterol could result from increased cholesterol synthesis and uptake with reduction in SR-BI-mediated efflux in ITf and from the overload of apoptotic cells, lowered ABCA1-mediated efflux and stimulated LDL-R protein synthesis in tubules in Pcsk9-/- mice. Concomitantly with the cholesterol accumulation, tubules showed infiltrates of immune cells, elevated IL-17A and IL-17RA, and changes in the immunotolerance homeostasis. PCSK9 deficiency decreased glucose in tubules and spermatozoa while increasing insulin2 in ITf and tubules not serum. Moreover, IR-α, and IR-β augmented in tubules but decreased in the anterior pituitary; IR-α increased whereas IR-β decreased in ITf. The histology and cholesterol levels were normal in Tg(PCSK9) mouse testis. The excess cholesterol creates a milieu favorable to the action of high IL-17A and IL-17RA, the development of inflammatory conditions and self-tolerance breakdown in testis.